State Investment in University Research and Commercialization: What Is Measurable and What Is Meaningful? - Burton, Kris (Maine Policy Review, 2014)
There are serious challenges in measuring the impact of universities on their state economies and in measuring the return on investment in universities by state legislatures. This article discusses the metrics currently used in looking at societal investment in research and the commercialization of research results. It asks if more meaningful metrics are needed, and if so, are they possible to obtain?
Keywords: Maine; R&D; research and development; universities; state legislatures